Principles of Interactive Computer Graphics / Second Edition - Newman H. William; Sproull F. Robert (Mcgraw Hill Book Company, 1979)
Preface, Basic Concepts, Introduction, Point-Plotting Techniques, Line-Drawing Displays, Two-Dimensional Transformations, Clipping and Windowing, Graphics Packages, Dispay File Compilation, Picture Structure, Interactive Graphics, Event Handling, Input Functions, Raster Graphics, Raster Graphics Fundamentals, Raster Display Hardware, Three-Dimensional Graphics, Curves and Surfaces, Perspective Depth, Shading, Graphics Systems, User Interface Design, Appendices, Bibliography, Index.